1982
DOI: 10.1007/bf01965411
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer activities of D-penicillamine copper complexes

Abstract: A comparison of the antiuleer activities of the polymeric cuprous, cupric disulfide and mixed valence D-penieillamine copper eomplexes in the Shay rat are presented. The data support the conclusion that these complexes may be less toxic and more effective than the parent compound in the therapy of arthritic diseases and/or ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A recent study on Cu-containing complexes has shown increased antiulcer activity [7]. Also, a comparable study of copper complexes in the sham rats has shown that those are less toxic and effective than parent compound in the therapy of arthritis and/or ulcers [8]. In Siddha system of medicine, copper-based herbomineral formulation is said to be effective against gastric ulcer, nodular inflammation, respiratory diseases, hepato-splenomegaly, and eye disorders [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on Cu-containing complexes has shown increased antiulcer activity [7]. Also, a comparable study of copper complexes in the sham rats has shown that those are less toxic and effective than parent compound in the therapy of arthritis and/or ulcers [8]. In Siddha system of medicine, copper-based herbomineral formulation is said to be effective against gastric ulcer, nodular inflammation, respiratory diseases, hepato-splenomegaly, and eye disorders [9].…”
Section: Introductionmentioning
confidence: 99%
“…Copper is an essential trace metal for living organisms and plays a major role in several enzymatic activities, in particular redox reactions which have an influence on the antioxidant system of the organism. 24 The medicinal properties of copper complexes in anti-inflammatory, antiarthritic, antiulcer and anticonvulsant diseases including anticancer properties [25][26][27][28][29][30][31] are also well documented. Due to the selective permeability of cancer cell membranes to copper complexes and their strict regulation on intracellular concentration encouraged the synthesis of copperbased compounds as probable antiproliferative agents with relatively less severe side effects than the present standard anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Copper complexes are potential reagents for the cleavage of DNA both oxidatively , and hydrolytically. Many of these complexes are found to be anti-inflammatory, antiarthritic, antiulcer, anticonvulsant, and antitumor agents . The selective permeability of cancer cell membranes to copper complexes and their strict regulations of the intracellular concentration have encouraged the synthesis of copper-based drugs as potential anticancer agents that are anticipated to have less severe side effects than standard anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The selective permeability of cancer cell membranes to copper complexes and their strict regulations of the intracellular concentration have encouraged the synthesis of copper-based drugs as potential anticancer agents that are anticipated to have less severe side effects than standard anticancer drugs. Several copper(I) complexes containing either pyridyl-type ligands such as 1,10-phenanthraline or mono- and bis(phosphine) ligands were screened for their anticancer activity, and some have shown good antiproliferative activity toward cancer cells.…”
Section: Introductionmentioning
confidence: 99%